Tradisi Babanyo di Kabupaten Bandung Barat untuk Bahan Pembelajaran di SMA - Fachrurrofi, Fachmi (LOKABASA, 2019)
The purpose of this study is to describe: 1) babanyo tradition in Cihampelas Kabupaten Bandung Barat; 2) semiotic elements contained in the babanyo tradition; and 3) teaching materials to read the articles of babanyo tradition for 12th grade of senior high school. The method used in this study was descriptive method by employing observation, interview, and documentation as its techniques. The data sources in this study were paraji (midwife) and mothers who knew and had carried out babanyo tradition. The results of this study are: 1) a description of the babanyo tradition which includes: conditions, objectives, property and food provided, and the steps in implementing the babanyo tradition, etc .; 2) the semiotic elements contained in  babanyo tradition are amounted to 30, which are the icons consisting of 13 elements, 3 indexes, and  14 symbols. The dominant aspect in this tradition is the symbol, this is due to the signs that included to the symbols have the highest total numbers, compared to the icons and the indexes. The signs are interrelated and have become a unit that forms a tradition; and 3) the results of this study can be used as an alternative learning material for articles reading in 12th grade of senior high school.AbstrakTujuan dari penelitian ini yaitu untuk mendeskripsikan: 1) tradisi babanyo di Kacamatan Cihampelas Kabupatén Bandung Barat; 2) unsur semiotik yang terdapat dalam tradisi babanyo; serta 3) bahan ajar membaca artikel tradisi babanyo di SMA kelas XII. Metode yang digunakan dalam penelitian ini yakni metode deskriptif dengan menggunakan teknik observasi, wawancara, dan dokumentasi. Sumber data dalam penelitian ini adalah paraji (dukun beranak) serta ibu-ibu yang tahu dan pernah melaksanakan tradisi babanyo. Hasil dari penelitian ini yaitu: 1) deskripsi mengenai tradisi babanyo yang mencakup: keadaan, tujuan, properti dan makanan yang disediakan, langkah-langkah dalam pelaksanaan tradisi babanyo, dsb; 2) unsur-unsur semiotik yang terdapat dalam tradisi babanyo berjumlah 30, yang terdiri dari ikon yang terdiri atas 13 unsur, indeks yang berjumlah 3, serta simbol yang berjumlah 14. Aspék yang dominan dalam tradisi ini adalah simbol, hal ini dikarenakan tanda yang termasuk kedalam simbol mempunyai jumlah paling banyak, dibandingkan dengan ikon dan indeks. Tanda-tanda tersebut saling berkaitan serta sudah menjadi satu kesatuan yang membentuk suatu tradisi; dan 3) hasil dari penelitian ini bisa dijadikan alternatif bahan pembelajaran membaca artikel di SMA kelas XII.